Marauders by gerry duggan, volume 3 ebook - Duggan, Gerry (Marauders (2019), 2021)
Collects Marauders (2019) #16-20, King in Black: Marauders (2021) #1. The Marauders must navigate difficult waters ahead! Double-dealing and backstabbing are the order of the day in the Hellfire Trading Company, but killing Kate Pryde crossed the line. The Black King must pay! And a resurrected Kate has some ideas about exactly how. Meanwhile, Storm faces off against her old rival Callisto in a rematch that's become very personal! And the Marauders return to Madripoor to pay tribute to a fallen friend - but old enemies are being forged anew, and the team is about to face a nasty surprise! Ororo's eyes are pointed to the future - one that takes her off the seas and over the horizon. And it all culminates in the biggest event of the season! Prepare for the Hellfire Gala - a night of dinner, drinking, diplomacy and deceit!